KOMPOSISI BENTOS YANG DITEMUKAN DI DANAU DIATAS KABUPATEN SOLOK - Eka Wahyuni Pratiwi; Rina Widiana; Abizar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Lake Diatas in Solok Regency is a lentic freshwater ecosystem experiencing increasing pressures from tourism, agriculture, and floating net cage aquaculture that may affect water quality so that it affects the life of organisms in the lake above. This study aimed to analyze the composition of benthic macroinvertebrates as bioindicators of water quality. The research was conducted from September to December 2025 using a descriptive survey method with purposive sampling across five observation stations. The results revealed nine benthic genera belonging to three phyla (Arthropoda, Annelida, Mollusca) and four classes (Insecta, Oligochaeta, Gastropoda, Bivalvia), with Thiara (Gastropoda) as the dominant genus and the highest density recorded at station V Density (K) 3611,11, Relative density (KR) 72,09.. The H’ values ranged 0.9213 - 1.3396, indicating heavily to moderately polluted conditions. Environmental parameters remained within ranges supportive of benthic life.